Preparation of Efficient Catalysts for Poly(ethylene-co-a-olefin), Poly(a-olefin), and Poly(ethylene-alt-carbon monoxide) - 박지혜 (The Graduate School, Ajou University, 2014)
This dissertation covers progress with transition metal polymerization catalysts for Poly(ethylene-co-α-olefin), Poly(α-olefin), and Poly(ethylene-alt-carbon monoxide). The complexes that we have designed were aimed at advantageous catalytic performances in terms of activity and polymer properties. Chapter 1 reviews the general transition metal complexes for Poly(ethylene-co-α-olefin), Poly(α-olefin), and Poly(ethylene-alt-carbon monoxide) in terms of mechanistic study after an introduction of historical background. Chapter 2 introduces the preparation of half-metallocenes of thiophene-fused and tetrahydroquinoline-linked cyclopentadienyl ligands for ethylene/-olefin copolymerization. Directed ortho-lithiation of the lithium carbamates generated from tetrahydroquinoline or tetrahydroquinaldine enables one-step preparation of thiophene-fused and tetrahydroquinoline-linked cyclopentadienes. 2,3,4,5-Tetramethyl-4,5-dihydrocyclopenta[b]thiophen-6-one was prepared without chromatography purification on the 40-g scale in a laboratory setting, from which the ligand precursor was obtained in 65% yield on a 50-g scale in a one-pot without the need for chromatography purification. Metallation was achieved in a high yield (78%) through reaction of the dilithiated compound with TiCl4. Many derivatives were prepared by employing the same synthetic scheme. The molecular structures of Me2Ti-complexes and Cl2Zr-complexs are determined by X-ray crystallography. Some complexes show excellent activities in ethylene/1-octene copolymerization, even when activated with small amount of MAO (Al/Ti = 1000) and give a high molecular-weight polymer. Chapter 3 presents morphology control of polymer particles in ethylene/carbon monoxide copolymerization using cationic palladium complexes containing bisphosphine and weakly coordinating anions. The catalyst should be harnessed with a lipophilic group on both the bisphosphine ligand framework and anion. In the bulk production of polymers, morphology control of the polymer particles without reactor fouling is crucial. This goal is achieved by employing the suspension polymerization technique in ethylene/CO copolymerization. Pressurizing with CO and ethylene gases on catalyst-containing 1-octanol droplets dispersed in water produces well-controlled polymer particles with bulk densities in the range of 0.20–0.30 gmL-1. Chapter 4 covers the preparation of ansa-zirconocene for production of Poly(-Olefin) Lubricants. The complex bearing methyl substituents at all positions adjacent to the bridgehead [(-C(Ph)HC(Ph)H-)(5-2,5-Me2C5H2)2ZrCl2] was synthesized in high yields (78%) through the reductive dimerization of 1,4-dimethyl-6-phenylfulvene utilizing ZrCl2•DME generated in situ. The structure of complex was subsequently confirmed using X-ray crystallography. This complex exhibited excellent catalytic performance with regard to 1-decene oligomerization, which was carried out with the intention of preparing lubricant base stocks. High activities were observed at temperatures as high as 120 °C and the oligomer distribution was appropriate for lubricant application. The methyl substituents at the positions adjacent to bridgehead in catalyst played a significant role in the catalytic performance. Appendix includes work toward the preparation of high-molecular-weight aliphatic polycarbonates by condensation polymerization of diols and dimethyl carbonate. In the first step, oligomers were formed bearing almost equal numbers of hydroxyl and methyl carbonate end-groups. In the second step, the condensation reaction was conducted at a high temperature (>180 oC) to connect the -OH and -OC(O)OCH3 chain-ends while removing the generated methanol under reduced pressure. Small amounts of sodium alkoxide (0.02-0.5 mol%) were used as a catalyst. Using an anhydrous diol was crucial for increasing the reaction rate and also for obtaining reproducible results. After polymerization, the basic catalyst was quenched with phthaloyl dichloride or melamine phenylphosphonate. This new strategy was valid for the preparation of high-molecular-weight polymers.
학위논문(박사)--아주대학교 일반대학원 :분자과학기술학과,2014. 8